Periodontitis and Systemic Lupus Erythematosus: A systematic review and meta‐analysis. (5th October 2021) - Hussain, Syed Basit; Leira, Yago; Zehra, Syeda Ambreen; Botelho, João; Machado, Vanessa; Ciurtin, Coziana; D'Aiuto, Francesco; Orlandi, Marco
Abstract: This systematic review and meta‐analysis evaluated the association between periodontitis (PD) and systemic lupus erythematosus (SLE). A systematic search was conducted through the following electronic databases: Cochrane Library, MEDLINE, EMBASE, Scopus, LILACS, CINAHL and SIGLE (System for Information on Grey Literature in Europe) for relevant publications up to September 2020 with no language restriction. The association between PD and SLE was assessed by the prevalence of PD in SLE patients (both sex and females only) as the primary outcome. Secondary outcomes included differences in common gingival parameters including probing pocket depth (PPD), clinical attachment level (CAL), disease activity index (SLEDAI) scores of SLE patients with or without PD. A total of 1183 citations and 22 full text articles were screened. Eighteen articles were included in the qualitative synthesis, and 13 in the quantitative analysis. SLE diagnosis was associated with greater odds of PD (OR = 1.33, 95% Confidence Interval [CI]: 1.20–1.48), but these were non‐significant when examined in females (OR = 3.20, 95%CI: 0.85–12.02). Patients with SLE exhibited no differences in PPD (SMD: −0.09 mm, 95%CI: −0.45–0.27) and CAL (SMD: 0.05 mm, 95%CI: −0.30–0.40) when compared with systemically healthy controls. PD diagnosis was, however, associated with higher SLEDAI scores in patients suffering from SLE (SMD: 0.68, 95% CI: 0.03–1.32). PD and SLE are both inflammatory diseases and their association could be bi‐directional. This review suggested that the patients with SLE have greater odds of suffering with PD. Further investigations are required to assess the association between PD and SLE.